2022
DOI: 10.7717/peerj.14318
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of epiphytic and intestinal bacterial communities in freshwater snails (Bellamya aeruginosa) living on submerged plants

Abstract: The combination of submerged plants and snails can combat eutrophication of freshwater systems by suppressing algal growth and assimilating nutrients. By consuming epiphytes, snails can benefit the growth of submerged plants. However, the efficiency of this phytoremediation strategy may depend on the microbes associated with the plants and snails. In this study, we compared the epiphytic bacterial communities on submerged plants (Vallisneria natans and Cabomba caroliniana) and intestinal bacterial communities … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 50 publications
(73 reference statements)
0
4
0
Order By: Relevance
“…For instance, biofilms can improve the host's resistance against pathogen invasion, while the presence of mobile elements can improve the host's tolerance to drug resistance (Palmer et al, 2010;Stokes and Gillings, 2011). Stress tolerance can further improve adaptability to environmental changes, such as temperature, salinity and contaminants (Fahy et al, 2008;Li et al, 2022;Liu et al, 2023). In this study, significant differences were found between the intestinal microbiome phenotypes of the three snail species, as evidenced from the results of BugBase.…”
Section: The Function Of Gut Microbiota In Snailsmentioning
confidence: 65%
See 3 more Smart Citations
“…For instance, biofilms can improve the host's resistance against pathogen invasion, while the presence of mobile elements can improve the host's tolerance to drug resistance (Palmer et al, 2010;Stokes and Gillings, 2011). Stress tolerance can further improve adaptability to environmental changes, such as temperature, salinity and contaminants (Fahy et al, 2008;Li et al, 2022;Liu et al, 2023). In this study, significant differences were found between the intestinal microbiome phenotypes of the three snail species, as evidenced from the results of BugBase.…”
Section: The Function Of Gut Microbiota In Snailsmentioning
confidence: 65%
“…These differences could be attributed to variations in the food composition or water environment. Although Planctomycetota was found to be highly abundant in all three snail species and also found in another study of Planorbidae snails (Van Horn et al, 2012), it has rarely been reported in other freshwater snails (Hu et al, 2018;Hu et al, 2021;Liu and Li, 2022;Zhou et al, 2022). In fact, it was only reported in 1 study on the intestinal microbiota of terrestrial Hydrobiidae (Walters et al, 2022).…”
Section: Diversity Of the Intestinal Bacterial Communities Of Freshwa...mentioning
confidence: 73%
See 2 more Smart Citations